2020
DOI: 10.2147/ott.s285536
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of LncRNA SNHG1 Were Suitable for Oncolytic Adenoviruse H101 Therapy in Oral Squamous-Cell Carcinoma

Abstract: Background As the most prevalent type of head and neck cancer, oral squamous-cell carcinoma (OSCC) accounts for nearly 90% of all oral cancer cases. Despite great progress having been made in the diagnosis and treatment of OSCC recently, the survival rate of OSCC patients has not risen remarkably. Chemotherapy is commonly used for OSCC treatment; however, the emergence of chemoresistance limits its long-term curative effect. Therefore, identifying effective biomarkers and molecular mechanisms is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Previous studies have focused on OSCC protein-coding genes (5,6). Recent studies have shown that lncRNA may serve an important role in the pathogenesis of OSCC (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on OSCC protein-coding genes (5,6). Recent studies have shown that lncRNA may serve an important role in the pathogenesis of OSCC (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed high expression of the oncogene SNHG1 in OSCC. More importantly, Wang et al (2020) also found that H101 could exert better antitumor effects in OSCC with high SNHG1 expression. Onyx-015 is an adenovirus with the E1B…”
Section: Oncolytic Viral Therapymentioning
confidence: 90%
“…Of these, SNHG1 can play its biological role via molecular mechanisms such as methylation [ 21 , 36 ], demethylation [ 51 ], and ubiquitination [ 45 ] in epigenetics. In the field of chemotherapy, SNHG1 has research potential [ 52 , 66 ]. These molecular mechanisms are worthy of in-depth exploration in the future.…”
Section: Discussionmentioning
confidence: 99%